In Vivo Labeling of Platelets with 75Se – Selenomethionine in Patients with Hepatic Cirrhosis and Thrombocytopenia. - Mayer, Manfred; Herrmann, Ilse; Kempgens, Uwe; Queisser, Wolfgang (Thrombosis and Haemostasis, 1977)
Labeling of platelets in vivo by 75Se – Selenomethionine (75Se-M) was performed in nine cases of hepatic cirrhosis and thrombocytopenia for evaluation of the kinetics of platelet maturation. Folic acid and vitamin B12 deficiency was excluded by pretreatment of the patients with these agents. The platelet maturation time – time between the injection of the isotope and maximum radioactivity of separated blood platelets – was shortened to 7.7±1.1 days (mean±SD) compared to the normal of 9.1±1.4 days. For explanation a disturbance of megakaryocyte maturation and/or platelet release from the bone marrow is suggested.